The source-to-sink system in continental rift lacustrine basins of the Nantun Formation in X Sag of the Tamtsag Basin, Mongolia - Liyuan Liu; Zongbao Liu; Rongsheng Zhao; Lin Cong; Xingquan Liu; Shiwei Xin; Zihao Mu (Scientific Reports)
Abstract The strata of the first member of the Nantun Formation constitute the primary targets for oil and gas exploration and development in X sag of the Tamtsag Basin. However, the distribution pattern of sand bodies within these strata remains poorly understood due to the complex interplay of factors such as provenance supply, boundary fault growth and evolution, and sediment transport pathways, which have led to diverse source-to-sink (S2S) systems. This study aims to provide a detailed characterization of these S2S systems. The results indicate the following: (1) Activity of the boundary faults within the first member of the Nantun Formation increased progressively, controlling paleovalley development and migration of the subsidence center and depocenter; (2) Three distinct S2S systems are identified in the study area: the “transverse drainage - fan delta” system, the “transverse drainage - braided delta” system, and the “axial drainage - braided delta” system, with their spatial distributions exhibiting significant inheritance; (3) Evolution of the S2S systems is governed by growth of the sag-controlling boundary faults and variations in provenance supply intensity.